Norman Rockwell : Artist and illustrator. - Buechner, Thomas S. (New York : Harry N. Abrams Inc. Publishers, 1970)
Norman Rockwell's subject is average America. He has painted it with such benevolent affection for so many years that a truly remarkable history of our century has been compiled. Through wars, depression, civil strife, and the exploration of space, he has drawn subjects from the everyday happenings of which most lives are made. Millions of people have been moved by the picture stories about the awkwardness of youth and the comforts of age, about pride in country, history, and heritage, about reverence, loyalty, and compassion. The virtues that he admires are very popular, and because he illustrates them using familiar people in familiar settings with wonderful accuracy, he describes the American Dream. These words from the text by Thomas S. Buechner, distinguished director of the Brooklyn Museum, explain Rockwell's enduring charm. and this volume, with its superb reproductions, including two-, three- and even four-page spreads and foldouts in full color, finally does justice to an artist whose works have most often been seen only in the impermanent mediums of magazines and calendars. The author discusses Rockwell's life and career, from his early training, through the development of his nature style, to his recent interest in the major social issues of our time ; particularly fascinating is the section devoted to the artist's technique, detailing the steps that may be involved from the first rough-idea sketch to the finished painting. Thanks to his exhausive study of Rockwell and his work, Buechner is able to draw a lively word-picture of an extraordinarily interesting personality - who also happens to be a unique phenomenon in the history of art - and places him in the great tradition of the story-telling artists of the past. More than 600 of Rockwell's best illustrations are reproduced, providing an unusually broad view of his work. He painted 317 Saturday Evening Post covers, all of which are included, along wiith representative covers and story illustrati
biog.
Engels
boek
Keywords: Rockwell, Norman; U.S.A.